Strategi Transformasi Tata Kelola Pembangunan untuk Mewujudkan Target Pertumbuhan Ekonomi Berkelanjutan Indonesia - Pambudi, Andi Setyo (Journal Transformation of Mandalika, e-ISSN: 2745-5882, p-ISSN: 2962-2956, 2025)
Indonesia is currently undergoing a transitional phase toward becoming a high-income country, yet remains trapped in the middle-income bracket due to inefficient public spending and fragmented governance. Key challenges include weak integration across planning, budgeting, implementation, and oversight, as well as limited coordination between central and regional governments. This study identifies a research gap in the absence of a unified framework linking Digital Public Infrastructure (DPI), Public Investment Management (PIM), and Benefits Realisation Management (BRM) within the policy cycle. The urgency is heightened by the 2025–2029 policy window, demographic bonus, and global industrial shifts. The research aims to design an integrated governance architecture, align institutional capacities across government levels, and formulate a roadmap for reform implementation. Using a qualitative-descriptive and exploratory approach, the study draws on policy analysis, national planning documents (RPJPN/RPJMN), and institutional matrices. Key findings reveal that digital reform must be supported by interoperable data systems, benefit registers, and performance dashboards. Recommendations include institutionalizing best practices, strengthening the role of data stewards, and developing success metrics that link micro-level outputs to macroeconomic impacts in a systematic and measurable way.